Design and motion planning of planar (3+1)-degree-of-freedom kinematically redundant RPR-RPRR parallel robots for optımal elımınatıon of actuatıon sıngularıtıes - Çubuk, Muhammed Yasir (My University, 2024)
Paralel robotlar, kapalı döngü yapıları sayesinde yüksek doğruluk, düşük atalet ve yüksek yük/ ağırlık oranı gibi çeşitli avantajlara sahiptir ve bu avantajlarıyla endüstriyel manipülatörler, tıbbi robotlar ve havacılık gibi farklı alanlarda kullanılmaktadırlar. Paralel robotların en büyük dezavantajı tekillik problemidir. Sonuçları açısından en kritik tekillikler Tip II tekillikler olarak da bilinen aktüasyon tekillikleridir. Artıklık, aktüasyon tekilliklerin eliminasyonunda kullanılan etkili bir yöntemdir. Bu tez çalışmasında, (3+1) serbestlik dereceli kinematik olarak artıksıl RPR-RPRR tipi düzlemsel paralel robotların aktüasyon tekilliklerinin optimal bir şekilde elimine edilmesi için gerekli tasarım ve hareket planlaması esasları çalışılmıştır. Robotun hareket denklemleri elde edilmiş, verilen bir hareketi gerçekleştirmesi için gerekli aktüatör torklarının ve kuvvetlerinin büyüklüklerinin hangi durumda sonsuza gidecekleri saptanmış ve aktüasyon tekilliklerini elimine etmek için artık serbestlik derecesinin optimal bir şekilde nasıl kullanılabileceği ortaya konulmuştur. Aktüasyon tekilliklerinin optimal eliminasyonunda, dinamik modeldeki ilgili matrisin kondisyon sayısı baz alınmıştır.

Parallel robots have various advantages such as high accuracy, low inertia and high payload-to-weight ratio thanks to their closed-loop structure, and with these advantages they are used in different fields like industrial manipulators, medical robots and aerospace. The biggest downside of parallel robots is their singularity problem. The most critical singularities in terms of results are actuation singularities, also known as Type II singularities. Redundancy is an effective method for eliminating singularities. In this thesis, the design and motion planning principles for the optimal elimination of actuation singularities of (3+1)-degree-of-freedom (DOF) kinematically redundant RPR-RPRR type planar parallel robots are studied. The equations of motion of the robot are obtained, the condition under which the values of the torques and forces that are supplied by the actuators to perform a given motion go to infinity is determined, and how the redundant DOF can be optimally used to eliminate actuation singularities is shown. The optimal elimination of actuation singularities is based on the condition number of the associated matrix in the dynamic model.
Düzlemsel (3+1) serbestlik dereceli kinematik olarak artıksıl RPR-RPRR paralel robotların aktüasyon tekilliklerinin optimal eliminasyonu için tasarımı ve hareket planlaması
Keywords: Makine mühendisliği; Mechanical engineering; Paralel manipülatörler; Robotics; Robotik; Robotlar; Robots; Singularity; Tekillik Parallel manipulators